1976
DOI: 10.1136/bmj.2.6045.1166
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative skin preparation: clinical evaluation of depilatory cream.

Abstract: Preoperative hair removal by a depilatory cream was compared with routine shaving. Although the incidence of wound infection was similar in both groups, cream depilation was found to be better. It was effective, atraumatic, non-toxic, and could be self-administered. Furthermore, it could be used safely on granulating

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…Another observational study showed significant reduction in SSIs when depilation was performed compared to shaving 23 . and yet another study included too few patients and was not considered as evidence in this evaluation 24 …”
Section: Resultsmentioning
confidence: 99%
“…Another observational study showed significant reduction in SSIs when depilation was performed compared to shaving 23 . and yet another study included too few patients and was not considered as evidence in this evaluation 24 …”
Section: Resultsmentioning
confidence: 99%
“…or quasi-RCTs[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] comparing the effects of preoperative hair removal versus no hair removal or different methods of hair removal (shaving, clipping, and depilatory cream) were identified and several meta-analyses were done.The three hair removal methods did not affect the incidence of SSIs compared with no hair removal. The combined ORs were 1•78 (95% CI 0•96-3•29) for shaving, 1•00 (0•06-16•34) for clipping, and 1•02 (0•42-2•49) for depilatory cream.…”
mentioning
confidence: 99%
“…In a meta-analysis comparing clipper hair removal, depilation and shaving (113)(114)(115)(116)(117)(118)(119) , the RR of 0.54 (95% CI 0.38-0.78) was significant and the incidence of SSI was significantly lower after clipper hair removal. In the comparison of depilatory cream and shaving, the SSI was lower after the depilatory cream, not significantly (120)(121)(122)(123)(124) (RR 0.52; 95% CI 0.24-1.11). In the comparison between no hair removal and shaving (113,121,(125)(126)(127)(128) , the RR was 0.58 (95% CI 0.34-0.98), which was significant, and the incidence of SSI was low in the absence of hair removal.…”
Section: Rationalementioning
confidence: 90%